Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To prove that if [tex]\(\operatorname{Sin} \alpha + \operatorname{Sin} \beta = \frac{1}{4}\)[/tex] and [tex]\(\operatorname{Cos} \alpha + \operatorname{Cos} \beta = \frac{1}{2}\)[/tex], then [tex]\(\tan \left( \frac{\alpha + \beta}{2} \right) = \frac{1}{2}\)[/tex], follow these steps:
1. Set up expressions using sum-to-product identities:
Let [tex]\(A = \frac{\alpha + \beta}{2}\)[/tex] and [tex]\(B = \frac{\alpha - \beta}{2}\)[/tex]. Then we can use the sum-to-product identities:
[tex]\[ \operatorname{Sin} \alpha + \operatorname{Sin} \beta = 2 \operatorname{Sin}\left( \frac{\alpha + \beta}{2} \right) \operatorname{Cos}\left( \frac{\alpha - \beta}{2} \right) = 2 \operatorname{Sin}(A) \operatorname{Cos}(B) \][/tex]
[tex]\[ \operatorname{Cos} \alpha + \operatorname{Cos} \beta = 2 \operatorname{Cos}\left( \frac{\alpha + \beta}{2} \right) \operatorname{Cos}\left( \frac{\alpha - \beta}{2} \right) = 2 \operatorname{Cos}(A) \operatorname{Cos}(B) \][/tex]
2. Substitute the given values:
Given [tex]\(\operatorname{Sin} \alpha + \operatorname{Sin} \beta = \frac{1}{4}\)[/tex]:
[tex]\[ 2 \operatorname{Sin}(A) \operatorname{Cos}(B) = \frac{1}{4} \][/tex]
[tex]\[ \operatorname{Sin}(A) \operatorname{Cos}(B) = \frac{1}{8} \quad \text{(1)} \][/tex]
Given [tex]\(\operatorname{Cos} \alpha + \operatorname{Cos} \beta = \frac{1}{2}\)[/tex]:
[tex]\[ 2 \operatorname{Cos}(A) \operatorname{Cos}(B) = \frac{1}{2} \][/tex]
[tex]\[ \operatorname{Cos}(A) \operatorname{Cos}(B) = \frac{1}{4} \quad \text{(2)} \][/tex]
3. Divide equation (1) by equation (2):
[tex]\[ \frac{\operatorname{Sin}(A) \operatorname{Cos}(B)}{\operatorname{Cos}(A) \operatorname{Cos}(B)} = \frac{\frac{1}{8}}{\frac{1}{4}} \][/tex]
[tex]\[ \frac{\operatorname{Sin}(A)}{\operatorname{Cos}(A)} = \frac{\frac{1}{8}}{\frac{1}{4}} \][/tex]
[tex]\[ \frac{\operatorname{Sin}(A)}{\operatorname{Cos}(A)} = \frac{1}{2} \][/tex]
4. Simplify to find [tex]\(\tan(A)\)[/tex]:
[tex]\[ \operatorname{Tan}(A) = \frac{1}{2} \][/tex]
Thus, we have shown that:
[tex]\[ \tan \left( \frac{\alpha + \beta}{2} \right) = \frac{1}{2} \][/tex]
1. Set up expressions using sum-to-product identities:
Let [tex]\(A = \frac{\alpha + \beta}{2}\)[/tex] and [tex]\(B = \frac{\alpha - \beta}{2}\)[/tex]. Then we can use the sum-to-product identities:
[tex]\[ \operatorname{Sin} \alpha + \operatorname{Sin} \beta = 2 \operatorname{Sin}\left( \frac{\alpha + \beta}{2} \right) \operatorname{Cos}\left( \frac{\alpha - \beta}{2} \right) = 2 \operatorname{Sin}(A) \operatorname{Cos}(B) \][/tex]
[tex]\[ \operatorname{Cos} \alpha + \operatorname{Cos} \beta = 2 \operatorname{Cos}\left( \frac{\alpha + \beta}{2} \right) \operatorname{Cos}\left( \frac{\alpha - \beta}{2} \right) = 2 \operatorname{Cos}(A) \operatorname{Cos}(B) \][/tex]
2. Substitute the given values:
Given [tex]\(\operatorname{Sin} \alpha + \operatorname{Sin} \beta = \frac{1}{4}\)[/tex]:
[tex]\[ 2 \operatorname{Sin}(A) \operatorname{Cos}(B) = \frac{1}{4} \][/tex]
[tex]\[ \operatorname{Sin}(A) \operatorname{Cos}(B) = \frac{1}{8} \quad \text{(1)} \][/tex]
Given [tex]\(\operatorname{Cos} \alpha + \operatorname{Cos} \beta = \frac{1}{2}\)[/tex]:
[tex]\[ 2 \operatorname{Cos}(A) \operatorname{Cos}(B) = \frac{1}{2} \][/tex]
[tex]\[ \operatorname{Cos}(A) \operatorname{Cos}(B) = \frac{1}{4} \quad \text{(2)} \][/tex]
3. Divide equation (1) by equation (2):
[tex]\[ \frac{\operatorname{Sin}(A) \operatorname{Cos}(B)}{\operatorname{Cos}(A) \operatorname{Cos}(B)} = \frac{\frac{1}{8}}{\frac{1}{4}} \][/tex]
[tex]\[ \frac{\operatorname{Sin}(A)}{\operatorname{Cos}(A)} = \frac{\frac{1}{8}}{\frac{1}{4}} \][/tex]
[tex]\[ \frac{\operatorname{Sin}(A)}{\operatorname{Cos}(A)} = \frac{1}{2} \][/tex]
4. Simplify to find [tex]\(\tan(A)\)[/tex]:
[tex]\[ \operatorname{Tan}(A) = \frac{1}{2} \][/tex]
Thus, we have shown that:
[tex]\[ \tan \left( \frac{\alpha + \beta}{2} \right) = \frac{1}{2} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.